ANALYSIS OF FEELING IN JOHN KEATS’ AND KATE CHOPIN’S LITERARY WORKS - Sri Winarsih (Universitas Musamus, 2018)
Some of the best literary works around the world are very good to learn, such as a poem “Ode on a Grecian Urn” by John Keats which is phenomenal by the quote “Beauty is truth, truth beauty”, and in prose, the work from Kate Chopin entitled The Awakening which is also phenomenal by the way the story ends. By using the theory of comparative literature, this study aims to describe the intense feeling of two different kinds of literary work by depicting their similarities and differences. The analysis shows that those works provide the description of different feeling delivered by each author. Keats presents the poetry in romantic mood, full of cheers and energy, although it serves momento mori. While Chopin presents the prose in elegiac or tragic mood. Those feeling are depicted throughout the way both authors represent the values of their works. Three values which are depicted in its similarities and differences are; 1) the meaning of death, 2) nature attribute, and 3) revealing truth. The feelings shown in the both literary works are basically about the reality of life. The beauty, the truth, the life, and the death are enclosed into the social life experienced by the people in the world. Keywords: comparative literature; feeling; values of literary works